2011
DOI: 10.1177/0333102411405228
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular migraine – validity of clinical diagnostic criteria

Abstract: Although VM diagnosis lacks a gold standard for evaluation of diagnostic criteria, repeated comprehensive neurotological evaluation after a long follow-up period indicates not only high reliability but also high validity of presented clinical criteria (positive predictive value 85%). Half of patients with pVM evolve to meet criteria for dVM. However, in a subgroup of VM patients with hearing loss, criteria for dVM and MD are not sufficiently discriminative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
86
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 31 publications
11
86
1
1
Order By: Relevance
“…The peak onset age of migraine in patients with VM was older than that of patients in dizziness clinic-based studies in Germany (32 vs. 20 years old) (1,4,13). Vertigo attacks appeared on an average of 6 years after migraine in 51% of patients, which was consistent with previous studies (1,4). Migraine syndromes in VM were restricted to MO and MA according to the ICHD-III beta, instead of migraine in the 2001 Neuhauser criteria (4).…”
Section: Discussionsupporting
confidence: 90%
“…The peak onset age of migraine in patients with VM was older than that of patients in dizziness clinic-based studies in Germany (32 vs. 20 years old) (1,4,13). Vertigo attacks appeared on an average of 6 years after migraine in 51% of patients, which was consistent with previous studies (1,4). Migraine syndromes in VM were restricted to MO and MA according to the ICHD-III beta, instead of migraine in the 2001 Neuhauser criteria (4).…”
Section: Discussionsupporting
confidence: 90%
“…The majority of VM patients with follow-up audiograms did not have deterioration of their PTA to meet MD criteria (11) or discrimination score to less than 80% (89-month mean audiogram follow-up) and, thus, did not move to the MDVM category. This sequence is consistent with a 9-year prospective study of definite and probable VM patients (45). Those authors observed the onset of progressive hearing loss leading to the additional diagnosis of MD in 8 (11%) of their subjects, raising the possibility that VM could be a risk factor for later MD development or that the 2 conditions share predisposing risk factors but manifest at different ages.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the diagnostic criteria published by Neuhauser et al [2], which have been proven valid and reliable [13], the diagnosis of VM can still be difficult. It is current practice to exclude relevant differential diagnoses in patients with suspected VM, to observe their response to migraine medication, and to follow up the patients.…”
Section: Discussionmentioning
confidence: 99%